Effects of aerobic exercise on event-related potentials related to cognitive performance: a systematic review - Gusatovic, Julia; Gramkow, Mathias Holsey; Hasselbalch, Steen Gregers; Frederiksen, Kristian Steen (PeerJ, 2022)
Introduction Aerobic exercise interventions may affect different cognitive domains such as attention, working memory, inhibition, etc. However, the neural mechanisms underlying this relationship, remains uncertain. Objective To perform a systematic review on exercise intervention studies that use event-related potentials (ERPs) as outcome for cognitive performance. Methods We identified studies through searches in four databases reporting the effects of either an acute bout or chronic exercise on any ERP associated with cognitive performance. Study population included participants >17 years of age with or without a diagnosis. Results A total of 5,797 records were initially identified through database searching of which 52 were eligible for inclusion. Most studies were of acute aerobic exercise with moderate intensity. Results were heterogenious across studies, but there was a trend that ERP amplitude increased and (to a lesser extent) latencies decreased post-exercise. The P3 ERP was the most often reported ERP. Conclusion Heterogeneity across studies regarding methodology limited the possibility to draw definitive conclusions but the most consistent findings were that acute aerobic exercise was associated with higher amplitudes, and to a lesser extent shorter latencies, of ERPs.
Keywords: Exercise; Aerobic exercise; Event-related potentials; ERP; EEG; Cognition; Electroencephalography; Cognitive task; Evoked potential